Episodic Memory in EFL Classroom at Bosowa University - Mardiana Mardiana; Baso Jabu; Sukardi Weda (ELT Worldwide: Journal of English Language Teaching, 2016)
The objectives of this research are (1) to find out whether the use of episodic memory is effective to improve the writing ability of the fifth-semester students of English education department of Bosowa University Makassar and (2) to find out the component of writing that improves the students’ writing the highest. The method applied in this research was true experiment design. It involved two groups design. That was experimental and control group. The subjects of this research were taken from two classes at fifth semester  A and B in 2014/2015 academic year. The sample consisted of 40 students. They were randomly formed. The data of this research was collected through writing test. The result of the research through students' writing test shows that the students' writing ability improved after treatment. It was supported by the rate of the mean score of writing which were observed in the students' posttest for the five components. The mean score of the experimental group was 71.89 which was higher than of the control group which was only 67.32 and the mean difference was 4.57. The content in the experimental group posttest were 83.50 while in the pretest only 67.50. The improvement of students' score in experimental for the content component was 16 point. It was the highest of all components of writing. It can be concluded that (1) The use of episodic memory is effective to improve the writing ability of the fifth-semester students of English Education Department of  Bosowa University Makassar; (2) The component of writing that improves the students’ writing the highest is content.Keywords: Episodic memory, writing ability.